Evaluation of White Matter Integrity Utilizing the DELPHI (TMS-EEG) System - Levy-Lamdan, Ofri; Zifman, Noa; Sasson, Efrat; Efrati, Shai; Hack, Dallas C.; Tanne, David; Dolev, Iftach; Fogel, Hilla (Frontiers in Neuroscience, 2020)
Objective: Evaluation of brain white matter fibers connectivity damage in stroke and traumatic brain injury (TBI) subjects by direct electrophysiological imaging (DELPHI) which analyzes TMS (transcranial magnetic stimulation) evoked potentials. Methods: Study included 123 participants out of which: 53 subjects with white matter related pathologies of (39 stroke, 14 TBI) and 70 healthy age-related controls. All subjects underwent DELPHI brain network evaluations of TMS-EEG evoked potentials, and DTI scans for quantification of white matter microstructure fractional anisotropy. Results: DELPHI output measures show a significant difference between healthy and strokegroups, a multidimensional approach was able to classify healthy from unhealthy with a balanced accuracy of 0.81±0.02 and AUC of 0.88±0.01 . Moreover, a multivariant regression model of DELPHI output measures achieved prediction of white matter microstructure changes measured by fractional anisotropy (FA) with highest correlations observed for fibers proximal to stimulation area such as frontal corpus callosum (r=0.7±0.02) ,anterior internal capsule (r=0.7±0.02) and fronto-occipital fasciculus (r=0.65±0.03). Conclusions: These results indicate that features of TMS evoked response are correlated to white matter microstructure changes observed in pathological conditions such as stroke and TBI, and that a multi-dimensional approach combining these features in supervised learning methods serve as a strong indicator for abnormalities and changes in white matter integrity.